Case Report: An Atypical Sellar Mass - Sellar Tuberculoma in a Young Patient - Arwa Moiz Jamali; Rakeshkumar Luhana (International Journal of Medical Students)
Background: Tuberculosis of the central nervous system is an uncommon but one of the most severe forms. It manifests as tuberculoma and tuberculous meningitis, with the majority of cases affecting children and immunocompromised patients. Overall, tuberculomas make up to 0.15–2 % of all intracranial lesions but sellar tuberculoma is extremely rare.